COMPARATIVE ANALYSIS OF GERMAN LOANWORDS IN ENGLISH - Imomkulov, Dilmurod (Журнал иностранных языков и лингвистики, 2023)
The article touches upon the topic of German borrowings in English and the peculiarities of their systematization. The article provides options for classifying the analyzed language units in accordance with the assimilation of words in the language and the time of their borrowing. English is the most widely-used language all over the world with 1.5 billion speakers. However up to this time English language has been enriched and developed through the words that came from other languages such as Latin, Greek, French, German, Russian, Arabic and other foreign languages. This article is aimed to analysis the loanwords from German language, their relation to linguistics. Furthermore, this research mostly looks at the origin of how and when the words came into English language and the acquisition of them by speakers. In this article we focus on the phonetic changings, semantics, morphological meanings, structures of the loanwords.